Hyponatremia, bone mineral density and falls in the elderly; Results from AHAP study - Hosseini Seyed Reza; Baghitabar Naghi; Mirzapour Ali; Oliaei Farshid; Nooreddini Hajighorban; Bijani Ali; Mouodi Simin (Sciendo, 2018)
Background. Hyponatremia (HN) can be associated with osteoporosis, falls and bone fractures in the elderly. Recent researches demonstrated different results about the correlation of HN with bone mineral density and bone fractures.